The Role of the Indonesian National Amil Zakat Agency in Social Finance Management As an Effort to Alleviate Poverty - Hasibuan, Riyadi; Pimada, Laila M.; Rabbani, Alfan Mufti; Malik, Syafiq (Maliki Islamic Economics Journal, 2022)
Poverty is one of the problems in everycountry, including Indonesia. Indonesia has enormous potential in utilizingIslamic economic instruments, namely zakat becauseit is a majority Islamic country and the country with the largest Muslim population in theworld. The large potential of zakat can be utilized by the Indonesian government in alleviating poverty in Indonesia, therefore this study was conducted to find out the role of BAZNAS Indonesia in managing social finance in an effort to alleviate poverty. The research method applie disusing a qualitative approach accompanied by a study of literature with reference materials are nationally accredited journals, books and articles relevant to research, and using various trusted websites. The National Amil Zakat Agency (BAZNAS) is an institution created by the government in collecting and distributing zakat. BAZNAS also has a special program for the welfare of the community, namely the existence of economic development programs, improving education, health and humanity. These programs show the seriousness of BAZNAS in alleviating poverty in Indonesia. The benefits of this research are as information and knowledge to the public regarding the performance of BAZNAS, as reference material for academics who want to do research, and other things